Closed for Business? Using a Mixture Model to Explore the Supply of Psychiatric Care for New Patients. (August 2019) - Rudoler, David; de Oliveira, Claire; Zaheer, Juveria; Kurdyak, Paul
Objective: To investigate the degree to which psychiatrists are accessible to new outpatients and the factors that predict whether psychiatrists will see new outpatients. Methods: We used administrative health data on all practicing full-time psychiatrists in Ontario, Canada, over a 5-year period (2009-2010 to 2013-2014). We used a regression model to estimate the number of new outpatients seen, accounting for case mix, outpatient volume, and psychiatrist practice characteristics. Results: Approximately 10% of full-time psychiatrists are seeing 1 or fewer new outpatients per month, and another 10% are seeing between 1 and 2 new outpatients per month. Our model identified psychiatrists in 3 distinct practice styles. One practice style (representing 29% of psychiatrists), on average, saw fewer than 2 new outpatients per month and 69 unique outpatients annually. Relative to other practice styles, they tended to see fewer patients with a previous psychiatric hospitalization and fewer patients who lived in lower income neighbourhoods. Conclusions: Nearly 1 in 3 full-time psychiatrists in Ontario see very few new outpatients. This has implications for access to care, particularly for outpatients with newly diagnosed mental illness. It also highlights the continued need to address access issues by assessing the role of psychiatrists within the Canadian health care system.